Objetos educacionais digitais e produção de textos escritos: contribuições do livro didático de língua portuguesa para o letramento digital - Silva, Ednaldo Gomes da (2017)
This paper is proposed to investigate the Digital Educational Objects, in the written text production axis, from the textbooks of Portuguese Language, and their contribution to the digital literacy. For this, we intend to feature the Digital Educational Objetcs – DEOs, identify and select written text production proposes and analyze them according to the National Curricular Parameters and the PNDL 2016 announcement that rules the insertion of the Digital Educational Objects into the textbook of Portuguese Language. According to Caiado and Gomes (2016), the Digital Educational Objects are technological tools that are integrated to the textbook in order to promote an interaction among students, contents and the textbook. This way, the teaching materials that arise in order to make the activities more interactive are learning objects developed and used in the digital environment, being, this way, necessarily a digital resource. The relevance of this research consists in the approach made of the Digital Educational Objects showing its impact in the teaching-learning process, besides analyzing the proposal of written text production activities on these digital educational objects. Therefore, this research has as theoretical contribution discussions: the textual linguistics represented by Marcuschi (2008) and Koch (2002), about Literacy in the vision of Soares (2004) and Kleiman (1995), Multiple literacy from Rojo (2009) and Street (2007), digital literacy from Xavier (2002) and the Digital Educational Objects from Leffa (2006), Wiley (2006) and Caiado (2006). The methodology will be done in a qualitative approach, because there will be an analyses of some interviews accomplished with three teachers, proposes of written text production found in the Digital Educational Objects from the Portuguese Language collection from the Elementary School. The final results demonstrate that the Digital Educational Objects are still too fragile to develop the Digital Literacy social practices when related to the proposal of written texts production, because they are too simple and present no complexity that requires some student's learning, and the student don't feel motivated to accomplish the activities.